The Arctic & Antarctica: Some Things Happen All At Once, Zeppelin Museum, Freidrichschafen, Germany, 29th January - 3rd April 2016 - Neudecker, Mariele (BathSPAdata, 2021)
Two pivotal research trips to Greenland in 2012 and 2015 extended Neudecker’s ongoing research into how the legacy of the Romantic Sublime and limited visual representations shape our perceptions of the Arctic regions. Questioning notions of wilderness in the context of current environmental and geopolitical realities this collection generates new perspectives on the Contemporary Sublime. This item contains an exhibition press release and 14 exhibition and installation views. This item documents Neudecker's key Arctic/Antarctica works exhibited as part of Some Things Happen All At Once her solo survey exhibition at the Zeppelin Museum in Freidrichschafen, Germany in 2016. 2 of the 3 Arctic works on show were drawn from responses to 2 research trips, in 2012 and then 2015 with Project Pressure to observe receding glaciers around Narsasuaq in Greenland. Firstly After Life 2016, a multi disciplinary installation that was made for this exhibition, with reference to Caspar David Friedrich's painting Sea In Ice, consisting of a model ship trapped in a constructed sea of ice, a vitrine work, a video on 3 wall hung monitors of fragmented ice on water, and 4 3D prints of the Arctic landscape: secondly On The Other Side 2016, a stainless steel stereoscopic viewer and photograph. The 3rd Arctic/Antarctica work shown was Some Things Happen All At Once 2014, a tank work based on the Halley Vl Antarctica Research Station, made for ANTARCTOPIA , an exhibition in the Antarctica Pavilion, at the Venice Architceture Bienale in 2014. An In Conversation during the exhibition between the artist and Claudia Emmert discussed the newly commissioned work After Life. Photography courtesy of the Zeppelin Museum. Used with permission. Work Specifications: After Life 2016 Mixed materials, Euro-pallet, corrugated cardboard, video on 3 monitors (duration: 42 min, 22 min, 15:10 min), giclée prints on archive pape r. On the Other Side 2016 Stainless steel and paper,Stereoscopic Viewer & Photograph, 90cm x 52cm x 30cm. Some Things Happen All At Once 2014 50 x 50 x42cm plus plinth glass, resin, water, GAC 100, salt. The work is under copyright and may not be used without permission. Use of this repository acknowledges cooperation with its policies and relevant copyright law .